Expanding the scope of “trans-humanism”: situating within the framework of life and death education – the importance of a “trans-mystical mindset” - Phan, Huy P.; Ngu, Bing Hiong; Hsu, Chao-Sheng; Chen, Si-Chi; Wu, Lijuing (Frontiers in Psychology, 2024)
Life and death education, as noted from the literatures, has been studied and researched extensively in China, Malaysia, and Taiwan. Our own research undertakings over the past several years, situated in different sociocultural settings have delved into aspects of life and death that could help advance theoretical understanding of the subject matters (e.g., does the meaning of 'effective life functioning' connote differing interpretations for different cultural groups?).Situating within the framework of life and death education, we expand the study of trans-humanism by introducing an extended prefix or nomenclature known as 'trans-mystical'. Specifically, our philosophized concept of trans-mysticism considers a related concept, which we term as a 'transmystical mindset'. A trans-mystical mindset, differing from an ordinary mindset, from our philosophical rationalization, is defined as "a person's higher-order state of consciousness, espousing her perception, judgment, belief, and attempted interpretation of life and death phenomena that are mystifying and fall outside the ordinary boundaries of human psyche". Our focus of inquiry, as reported in the present article, seeks to advance our proposition: that a transmystical mindset, unlike an ordinary mindset, may help a person to rationalize, appreciate, and understand metaphysical contexts, mystical experiences, and the like. This focus, interestingly, serves to highlight an important discourse -namely, that there is a dichotomy in theoretical lenses (i.e., objective reality vs. individual subjectivity) that a person may use to rationalize the significance or non-significance of universal contexts, events, phenomena, etc. (e.g., a person's experience of 'premonition'). As such, then, there is an important question that we seek to consider: whether philosophization, or the use of philosophical psychology, would yield perceived 'scientific evidence' to support or to reject the study of metaphysicism, mysticism, and the like? For example, does our philosophization of an 'equivalency' between a person's trans-mystical mindset and her experience of self-transcendence help to normalize and/or to scientize the subject matters of metaphysicism, mysticism, etc.?